A Rare Case of Evan Syndrome with Portal Hypertension - Sinha, Rahul; Bajpai, Mukul; Dalal, Shamsher; Sodhi, Kirandeep (Journal of Hematology Research, 2014)
Evan’s syndrome was first described in 1951 by Evan’s and associates. It has long been considered as a coincidental combination of ITP and AIHA and or immune neutropenia in the absence of any underlying cause. We report this rare condition in a 9-year-old male who presented with severe pallor and multiple ecchymotic patches over arms and abdomen with portal hypertension.